The mitigative effect of lotus root (Nelumbo nucifera Gaertn) extract on acute alcoholism through activation of alcohol catabolic enzyme, reduction of oxidative stress, and protection of liver function - Yang, Zihan; Gao, Yuan; Wu, Weijie; Mu, Honglei; Liu, Ruiling; Fang, Xiangjun; Gao, Haiyan; Chen, Hangjun (Frontiers in Nutrition, 2023)
Objectives Lotus root (Nelumbo nucifera Gaertn) is a common medicinal-food dual-use vegetable. In this study, the effects of lotus root extract on acute alcoholism were investigated. Methods The Walle-Hoch method was used to determine the ADH activity of lotus root extracts in vitro. Lotus root methanol extract were identified by UPLC-QTOF-MS/MS based metabolomics analysis. Then 109 active ingredients with achievable oral doses and drug-like properties were explored using the TCMSP platform. SwissTargetPrediction Database to predict lotus root treatment targets for acute alcoholismSTRING database (https://www.string-db.org/) was used to construct protein-protein interaction network graphs. Gene ontology (GO) functional, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of genes common to lotus root and alcoholism by Metascap database. Molecular docking simulations were performed using AutoDock 1.5.6 software. Animal experiments verified the relieving effect of lotus root extract on acute alcoholism after intervention. Results Results indicated the methanol extract of lotus root showed the highest activation rate of ethanol dehydrogenase in vitro (18.87%). The 433 compounds of lotus root methanol extract were identified by UPLC-QTOF-MS/MS based metabolomics analysis. Bioinformatics analysis indicate that there were 224 intersectioning targets between lotus root extract and acute alcoholism. KEGG enrichment analysised shows that lotus root extract may play a role in treating acute alcoholism by intervening with the neuroactive ligand-receptor interaction pathway. The protein-protein interaction network (PPI) analysis found that HSP90AA1, MAPK1 and STAT3 played a key role in lotus root extract-modulated PPI networks. Molecular docking showed that (7R, 8S)-dihydrodihydrodipine cypressol had the best binding ability with MAPK1. Experiments in mice indicate that lotus root extract improved the activity of liver alcohol dehydrogenase (ADH), acetaldehyde dehydrogenase (ALDH), catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX), increase glutathione (GSH) and reduce malondialdehyde (MDA) levels, decrease glutamate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (AKP) in the serum of mice with acute alcoholism, and accelerate the metabolic rate of alcohol after drinking. This study reveals the mechanism of lotus root to alleviate acute alcoholism, which provides a basis for further research on functional foods using lotus root and offers new possibilities for the treatment of acute alcoholism. Conclusions The results of the current study showed that the methanolic extract of lotus root had the highest activation rate of ethanol dehydrogenase. Network pharmacology results suggest that lotus root extract may play a role in the treatment of alcoholism by regulating signaling pathways, such as neuroactive ligand-receptor interactions, as well as biological processes, such as regulation of secretion, regulation of ion transport, response to lipopolysaccharides, and response to alcohol. Animal experiments confirmed the therapeutic effect of lotus root on acute alcoholism mechanistically through activation of alcohol catabolic enzyme, reduction of oxidative stress and protection of liver function.